BADAN REGULATOR PENYIARAN DALAM PERSPEKTIF HUBUNGAN ANTARA NEGARA, PASAR, DAN MASYARAKAT MADANI (SEBUAH STUDI KASUS TERHADAP SEJARAH EKSISTENSI KPI SEBAGAI PENDUKUNG DEMOKRATISASI RANAH PUBLIK) - Nadiah Abidin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2007)
Broadcasting belongs to the regulating class. This is why vested interests are attached to it. In concrete, there are three major groups that can be identified: The state, the market, and the civil society. Along with the wind of democracy, accured ideas on building an auxiliary state agency outside the governmental structure to regulate broadcasting which in turn gave birth to KPI. Aware of the rising interest disputes, the main problem that wants to be discussed is the problems faced by KPI in the Indonesian formal legal system seen from its historical background in order to understand the conditions of KPI today and predict its condition in the future. The type of study used in this research is qualitative, subjected at group units based on the critical paradigm with multiple case analysis. Based on the research result the Indonesian public administration has not yet been able to adopt a thorough institutional reformation in the broadcasting world which is represented by KPI. The problem lies in the natural characteristic of each interest group that haven’t found a middle way to balance their positions. As a result, disputes are unavoidable and keep conflicting. In turn, to maintain the existence of KPI, the body itself must actively accelerate the awareness and movement of the civil society without neglecting the importance to continue lobying and peacefully negotiating with the state and the market.